Steviol glycoside production and growth in Stevia rebaudiana shoot culture after methyl jasmonate elicitation - Rahmawati, Andira; Iriawati,; Esyanti, Rizkita Rachmi; Roohaida Othman, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Steviol glycosides are a group of compounds derived from the Stevia rebaudiana metabolites which are commonly used as sugar replacements. Methyl jasmonate (MeJA) elicitation is one strategy to induce high steviol glycoside content. MeJA can enhance the synthesis of secondary metabolites, however, it can also negatively impact the growth of Stevia. The objective of this study was to establish the concentration and exposure duration of MeJA elicitation to obtain the highest level of steviol glycoside production while achieving the best growth for Stevia shoot cultures. The shoot cultures were elicited using MeJA at concentrations of 10 μM, 50 μM, and 100 μM for 24, 48, and 72 h. The cultures were then transferred into the medium without MeJA for 7 days, and then growth characteristics were measured. Analysis of stevioside and rebaudioside A levels was performed using HPLC from samples harvested directly after treatment and 7 days post-elicitation. MeJA was found to suppress growth in terms of height, adventitious shoot formation, and leaf size across all concentrations. However, the number of leaves, fresh weight, number of axillary buds, and number of nodes showed no significant difference. The optimal condition for stevioside synthesis was achieved at 50 μM MeJA for 48 h (0.73 mg/g), while the optimal condition for rebaudioside A synthesis was achieved with 100 μM MeJA 24 h treatment (0.63 mg/g). Analysis of the plant growth and secondary metabolite production suggested that the treatment using 50 μM MeJA for 48 h was found to be the best conditions which gave high secondary metabolite production while plant growth was also high. This finding can serve as a fundamental approach for enhancing the production of steviol glycosides in the industry.